Asymptomatic Nonsyndromic Multiple Supernumerary Premolars - Gupta, Seema (Jaypee Brothers Medical Publishers, 2012)
The apparently morphologically normal finding of multiple supernumerary teeth in absence of an associated systemic condition or syndrome is an uncommon phenomenon. Surgical removal of supernumerary teeth is indicated if eruption of the adjacent teeth has been delayed; altered eruption, displacement of adjacent teeth is evident or pathologies such as cystic lesion and resorption of adjacent tooth have occurred. If the risks of surgery outweigh the benefits of removal, the teeth may be left in situ and a regular radiographic monitoring should be made. How to cite this article: Gupta S, Goswami M. Asymptomatic Nonsyndromic Multiple Supernumerary Premolars. Int J Clin Pediatr Dent 2012;5(1):84-86.